TURKISH SHIPBUILDING INDUSTRY - CHALLENGES AND POTENTIAL - Turan, Eda; Cengiz, Hulya (BRODARSKI INST, 2015)
Shipbuilding industry was developed and grown in the late 19th and early 20th centuries. The Turkish shipbuilding industry started to develop in an international level around 15 years ago with specialization in small tonnage vessels. The global economic crisis that started in 2008 has affected the enhancement of shipbuilding industry in Turkey. This study addresses the important factors affecting the development of Turkish shipbuilding industry by focusing on the global shipbuilding during the crisis and the current state of the industry with the application of a survey to the key decision makers. The data was obtained from the survey collected from the Turkish shipyards and maritime companies that represent the considerable share of the industry. The surveys were conducted between 2012 and 2013. The current state of shipbuilding industry concerning the most relevant factors for the development of the industry according to the respondents has been designated, and it was seen that the highlighted factors were lower in the current state of the industry. Moreover, the strongest and weakest factors for the Turkish shipbuilding industry were pointed out. Herein, general views of the respondents regarding the development of Turkish shipbuilding industry were presented.
Keywords: Turkish shipbuilding; shipyard; Turkey; shipbuilding; sectoral analysis; survey; INPUT-OUTPUT-ANALYSIS; NATIONAL-ECONOMY; SECTOR; Engineering